High-Level Teleoperation System for Aerial Exploration of Indoor Environments - Isop, Werner Alexander; Gebhardt, Christoph; Nägeli, Tobias; Fraundorfer, Friedrich; Hilliges, Otmar; Schmalstieg, Dieter (Frontiers in Robotics and AI, 2019)
Exploration of challenging indoor environments is a demanding task. While automation with aerial robots seems a promising solution, fully autonomous systems still struggle with high-level cognitive tasks and intuitive decision making. To facilitate automation, we introduce a novel teleoperation system with an aerial telerobot that is capable of handling all demanding low-level tasks. Motivated by the typical structure of indoor environments, the system creates an interactive scene topology in real-time that reduces scene details and supports affordances. Thus, difficult high-level tasks can be effectively supervised by a human operator. To elaborate on the effectiveness of our system during a real-world exploration mission, we conducted a user study. Despite being limited by real-world constraints, results indicate that our system better supports operators with indoor exploration, compared to a baseline system with traditional joystick control.